Pyrolysis of plastic waste for a better environmental system. (2022) - Sasikumar, C.; Kannan, R.; Senthilkumar, C.; Sarweswaran, R.; Nagaraja, M.; Sundaresan, R.
Abstract: Owing to the rapid utilization of fossil fuels, the world is in need of a sustainable and renewable energy source. Surplus resources of municipal solid waste and plastic waste will act as a better biomass fuel for generating electricity and liquid fuels, which can be extracted using Pyrolysis process. The present work addresses the pyrolysis process of mixed plastic wastes. This leads to fuel oil production, which is capable to reduce the problems associated with plastic waste disposal. Plastic wastes along with municipal solid waste getting generated day to day in diversified house hold and industrial wastes are addressed to be a threat and among the major sources of environmental pollution. On other hand it's to be noticed that theses carbonaceous plastics wastes and municipal solid waste having rich carbon content. This Biomass wastes are highly capable not only to provide a renewable source of fuel but also these technologies will act as a gate way of recycling the multidisciplinary waste getting generated in the society.